Magnesium ions mediate ligand binding and conformational transition of the SAM/SAH riboswitch - Hu, Guodong; Zhou, Huan-Xiang (Communications biology, 2023)
The SAM/SAH riboswitch binds S-adenosylmethionine (SAM) and S-adenosylhomocysteine (SAH) with similar affinities. Mg 2+ is generally known to stabilize RNA structures by neutralizing phosphates, but how it contributes to ligand binding and conformational transition is understudied. Here, extensive molecular dynamics simulations (totaling 120 μs) predicted over 10 inner-shell Mg 2+ ions in the SAM/SAH riboswitch. Six of them line the two sides of a groove to widen it and thereby pre-organize the riboswitch for ligand entry. They also form outer-shell coordination with the ligands and stabilize an RNA-ligand hydrogen bond, which effectively diminishes the selectivity between SAM and SAH. One Mg 2+ ion unique to the apo form maintains the Shine–Dalgarno sequence in an autonomous mode and thereby facilitates its release for ribosome binding. Mg 2+ thus plays vital roles in SAM/SAH riboswitch function. Molecular dynamics simulations reveal site-specific mechanisms of Mg2+ ions in conformational transitions of the SAM/SAH riboswitch for ligand and ribosome binding.